2017
DOI: 10.1097/md.0000000000006537
|View full text |Cite|
|
Sign up to set email alerts
|

Associations between polymorphisms in coagulation-related genes and venous thromboembolism

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The occurrence of the thromboembolic disease is in the line with the simultaneous presence of a gene polymorphisms and environmental risk factors which can partly explain the inconsistent results of similar studies conducted in different geographic regions 10,11,34 . The results of our study show that the presence of polymorphisms FII G20210A and FV G1691A is significantly higher in the VTE group compared to a healthy control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of the thromboembolic disease is in the line with the simultaneous presence of a gene polymorphisms and environmental risk factors which can partly explain the inconsistent results of similar studies conducted in different geographic regions 10,11,34 . The results of our study show that the presence of polymorphisms FII G20210A and FV G1691A is significantly higher in the VTE group compared to a healthy control group.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggested a multifactorial etiology of VTE. Therefore, the hereditary predisposition only represents an increased risk and does not determine if the disease will necessarily manifest in genetically affected population [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…However, that meta-analysis only included 5 studies, and the analysis was only conducted with the additive model. The other meta-analysis study showed a non-significant conclusion for the pooled overall OR when removing the groups from Bezemer et al’s study [24]. In our study, the meta-analysis was performed by using three different genetic models and showed a significant association between rs13146272 and VTE.…”
Section: Discussionmentioning
confidence: 45%
“…Although previous studies have shown a significant association between rs13146272 and VTE ( p < 1.7e −07 ), this value is still far from the threshold for genome-wide significance ( p < 5.0e −08 ) [21, 23]. In addition, a meta-analysis study by Jiang et al [24] included only partial genotype data for rs13146272, possibly leading to biased outcomes. In addition, most previous studies used only the additive model for genetic analysis to evaluate the odds ratio of the variants in VTE.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it provided adjusted thresholds for both statistical significance and futility according the quantified strength of the evidence and the impact of multiplicity. [ 27 ] We constructed Z -curves for both primary and secondary outcomes, and alpha conventional threshold for significance testing was set at 5%. The expected intervention effect may be achieved and no further trials required when the cumulative Z -curve crosses the trial sequential monitoring boundary or enters the futility area.…”
Section: Methodsmentioning
confidence: 99%